Post-Pandemic Inclusive Learning Management Strategies: A Case Study of Integrated Islamic School - Ali Akbarjono; Dita Lestari; Arisca Nanda Rahmayani (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2024)
ENGLISH: Post-Pandemic Inclusive Learning Management Strategies: A Case Study of Integrated Islamic SchoolObjective: This study aims to explore post-pandemic inclusive learning management strategies in Integrated Islamic Schools. Method: This research uses the Participatory Action Research (PAR) method. This research was conducted at SD IT Al-Aufa Bengkulu and SD Alam Mahira Bengkulu in 2024. Data collection was done using observation, interviews, and document studies. Data analysis uses triangulation. Results: Integrated Islamic Schools in Bengkulu can be a relevant model for other educational institutions that want to improve inclusivity, flexibility, and learning effectiveness. Conclusion: An inclusive, technology-based learning management strategy supported by Islamic values can be a solution to overcome learning challenges in the post-pandemic era. Challenges such as limited resources, technology gaps, and the need for customized learning interventions still exist. Contribution: This research contributes to the development of an inclusive learning model that can be adopted by Islamic schools, taking into account the local context in Bengkulu.INDONESIAN: Strategi Manajemen Pembelajaran Inklusi Pasca-Pandemi: Studi Kasus di Sekolah Islam TerpaduTujuan: Penelitian ini bertujuan mengeksplorasi strategi manajemen pembelajaran inklusi pasca-pandemi di Sekolah Islam Terpadu. Metode: Penelitian ini menggunakan metode Parcipatory Action Research (PAR). Penelitan ini dilakukan di SD IT Al-Aufa Bengkulu dan SD Alam Mahira Bengkulu tahun 2024. Pengumpulan data menggunakan observasi, wawancara, dan studi dokumen digunakan dalam proses pengumpulan data. Analisis data menggunakan triangulasi dalam proses analisis data. Hasil: Sekolah Islam Terpadu di Bengkulu dapat menjadi model yang relevan bagi lembaga pendidikan lain yang ingin meningkatkan inklusivitas, fleksibilitas, dan efektivitas pembelajaran. Kesimpulan: Strategi manajemen pembelajaran inklusif, berbasis teknologi, dan didukung oleh nilai-nilai Islam dapat menjadi solusi untuk mengatasi tantangan pembelajaran di era pascapandemi. Tantangan seperti sumber daya yang terbatas, kesenjangan teknologi, dan kebutuhan akan intervensi pembelajaran yang disesuaikan masih ada. Kontribusi: Penelitian ini memberikan kontribusi dalam pengembangan model pembelajaran inklusif yang dapat diadopsi oleh sekolah-sekolah Islam, dengan memperhatikan konteks lokal di Bengkulu